Etika Komunikasi dalam Mitigasi Bencana Berbasis Kearifan Lokal; Tradisi Temanten Kucing Desa Pelem, Kecamatan Campurdarat, Kabupaten Tulungagung - Hakim, Lukman; Putro, Widiyatmo Eko; Rusmana, Dewi Sri Andika (representamen, 2018)
Indonesian people in each region have a wealth of local knowledge commonly referred to as local wisdom. The long-term goal of this research is to preserve and preserve local knowledge which is still relevant today. Traditional methods like this, in addition to obtaining benefits in their respective fields can also create harmony and unity among citizens. Because, local wisdom as one of the nation's adhesive tools in addition to the lack of harmony in society today. Communication ethics is a formal object and disaster mitigation in the â€œtemanten kucingâ€ tradition of Tulungagung is a material object. The method used in this study is hermeneutics by conducting a literature review to achieve the target. The results obtained are the understanding of heuristics by placing, description, interpretation, internal coherence and historical continuity so as to obtain a new synthesis that in this tradition there is a teleological-utilitarian content that is full of social and political nuances. Communication is done for the realization of a harmonious social climate and has a special character in creating certain goals. It can be concluded that communication ethics in the â€œtemanten kucingâ€ tradition contains certain values of teleological ethics (aiming) to lead the masses. This ceremony is aimed at goals (telos) values of wisdom and unity.Keywords: communication ethics, local wisdom, disaster mitigation